A new species of the genus Burmagomphus Williamson (Odonata: Gomphidae) from Northern Thailand - Makbun, Noppadon (Zootaxa, 2017)
Burmagomphus chiangmaiensis sp. nov. (holotype: Ban Luang, Chom Thong, Chiang Mai province, Thailand, 890-900 m, 14 v 2012) is described and illustrated. It can be differentiated from its most similar congener, B. apricus from China, by shape of posterior hamulus, yellow trapezoid band on occiput, and larger size.